Pengaruh Komitmen Organisasi dan Organizational Citizenship Behavior terhadap Turnover Intention Pada Guru SMK Swasta Wilayah Kecamatan Koja - Muhammad Raditio; Widya Parimita; Suherdi (Jurnal Bisnis, Manajemen, dan Keuangan, 2023)
ABSTRACT This study aims to determine the effect of organizational commitment and organizational citizenship behavior simultaneously on turnover intention in private vocational schoolteachers in Koja District, North Jakarta. This type of research includes explanatory research with a quantitative approach. The sample in this study amounted to 110 people based on calculations with the Slovin formula of 5% error estimation. While the sampling technique is a random sampling area. The method of collecting data is through a questionnaire that has been tested with Google Forms. Data analysis used multiple linear regression, hypothesis testing, and coefficient of determination with IBM SPSS 23. The results showed that organizational commitment and citizenship behavior simultaneously significantly negatively affected private SMK teachers' turnover intention in Koja District, North Jakarta. This effect means that the higher the level of organizational commitment and organizational citizenship behavior, the behavior of turnover intention will decrease, and vice versa, the lower the level of organizational commitment and organizational citizenship behavior, the behavior of turnover intention will increase. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh komitmen organisasi dan organizational citizenship behaviour secara simultan terhadap turnover intention pada guru SMK swasta Kecamatan Koja, Jakarta Utara. Jenis penelitian termasuk penelitian eksplanatori dengan pendekatan kuantitatif. Sampel dalam penelitian ini berjumlah 110 orang berdasarkan perhitungan dengan rumus slovin estimasi eror 5%. Sedangkan teknik pengambilan sampel area random sampeling. Metode pengumpulan data melalui kuesioner yang sudah di uji coba dengan google form. Analisis data menggunakan regresi linier berganda, uji hipotesis dan koefisien determinasi dengan IBM SPSS 23. Hasil penelitian menunjukkan bahwa komitmen organisasi dan organizational citizenship behaviour secara simultan berpengaruh negatif signifikan terhadap turnover intention pada guru SMK swasta Kecamatan Koja, Jakarta Utara. Pengaruh ini memiliki arti semakin tinggi tingkat komitmen organisasi dan organizational citizenship behaviour, maka perilaku turnover intention akan menurun, begitu juga sebaliknya semakin rendah tingkat komitmen organisasi dan organizational citizenship behaviour, maka perilaku turnover intention akan meningkat.